Syphilis iridocyclitis in a patient with type 1 diabetes. Issue 4 (25th December 2015) - Comassi, Mario; Natali, Andrea; Solini, Anna
Abstract: We present a rare cause of iridocyclitis in a patient with vitiligo and type 1 diabetes who showed poor metabolic control, and suffered from remitting fever, weight loss, fatigue, diffuse arthralgias and reduced visual acuity. Mild systemic symptoms coupled with increased cholestasis enzymes, insulin resistance, mild inflammation and a functioning adrenal gland focused our clinical work‐up on granulomatous causes of iridocyclitis. Specific tests confirmed syphilis, with no involvement of the central nervous system. Ocular syphilis, despite being unusual, can be the only manifestation of the disease. The work‐up of any unexplained ocular inflammation should include testing for syphilis so as to not delay the diagnosis. Abstract : We describe here a relatively rare case of iridocyclitis as sole manifestation of syphilis in a patient with type 1 diabetes.